⎩ ⎪ ⎪ ⎨ ⎪ ⎪ ⎧ x + y + z = 3 π / 4 tan ( x ) + tan ( y ) + tan ( z ) = 5 tan ( x ) tan ( y ) tan ( z ) = 1
x , y , z are real numbers satisfying the system of equations above Find the value of tan 3 ( x ) + tan 3 ( y ) + tan 3 ( z ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
There isn't a need to use Vieta's.
We know that a 3 + b 3 + c 3 = ( a + b + c ) 3 − 3 ( a + b + c ) ( a b + b c + c a ) + 3 a b c (which is a "well-known algebraic identity", which also follows from Newton's identities).
Yeah U r right.....but why I did that unconsciously because I thought that way when I posed the problem
I am getting the answer as 68.please point out the mistake. tan ( x + y ) = 1 − t a n z − 1 − tan z ⟹ ( tan x + tan y ) = 1 + tan z ,similarly we would get three equations like this.Adding the three we would get the value of \ ∑ c y c tan x tan y = 4 . From this we would get tan 2 x + tan 2 y + tan 2 z = 1 7 After substituting in the identity ( a 3 + b 3 + c 3 − 3 a b c = ( a + b + c ) ( a 2 + b 2 + c 2 − a b − b c − c a ) we get the value of our required expression 68. @Ravi Dwivedi @Calvin Lin
Log in to reply
How did you get from the first line to the second?
I also do not see how "adding the three gives us tan x tan y = 4 ". If anything, I get ∑ tan x = 1 (which contradicts a given condition).
Problem Loading...
Note Loading...
Set Loading...
Using the formula tan ( x + y + z ) = 1 − tan x ⋅ tan y − tan y ⋅ tan z − tan z ⋅ tan x tan x + tan y + tan z − tan x ⋅ tan y ⋅ tan z we have
− 1 = tan 4 3 π = 1 − tan x ⋅ tan y − tan y ⋅ tan z − tan z ⋅ tan x 5 − 1 ⟹ tan x ⋅ tan y + tan y ⋅ tan z + tan z ⋅ tan x = 5 Using Vieta's relations we conclude that tan x , tan y , tan z are roots of the polynomial t 3 − 5 t 2 + 5 t − 1 = 0 tan 3 ( x ) = 5 tan 2 ( x ) − 5 tan x + 1 tan 3 ( y ) = 5 tan 2 ( y ) − 5 tan y + 1 tan 3 ( z ) = 5 tan 2 ( z ) − 5 tan z + 1
Adding these three equations we get
tan 3 ( x ) + tan 3 ( y ) + tan 3 ( z ) = 5 ( tan 2 ( x ) + tan 2 ( y ) + tan 2 ( z ) ) − 5 ( tan x + tan y + tan z ) + 3
tan 3 ( x ) + tan 3 ( y ) + tan 3 ( z ) = 5 ( ( tan x + tan y + tan z ) 2 − 2 ( tan x ⋅ tan y + tan y ⋅ tan z + tan z ⋅ tan x ) ) − 5 ( tan x + tan y + tan z ) + 3
tan 3 ( x ) + tan 3 ( y ) + tan 3 ( z ) = 5 ( 5 2 − 2 ( 5 ) ) − 5 ( 5 ) + 3 = 5 3